Neuroendocrine tumor in the vaginal reconstruction of a patient with Mayer-Rokitansky-Küster-Hauser syndrome and anorectal malformation - Nicholas Fioravante; Tara Tronetti; Eric Strauch; Roger Voigt; Kimberly Lumpkins (Elsevier, 2021)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome occurring in association with an anorectal malformation (ARM) is rare but well described (Wester et al., 2012) [1]. In some patients with MRKH and ARM, a rectovestibular fistula may be left in situ as a neovagina [2,3]. Previously, adenocarcinomas arising in vaginal reconstructions have been reported, however neuroendocrine tumors (NET) have not been previously described in this setting [4,5]. We describe the case of a patient with MRKH associated with ARM that developed a neuroendocrine tumor of the neovagina constructed in infancy from a rectovestibular fistula. She was immunosuppressed following a living related kidney transplant at age 11. At age 20, vaginal bleeding was noted. A 1.5 cm neuroendocrine tumor was found on the anterior vaginal wall and she underwent a complete full-thickness transvaginal resection. The management considerations for neuroendocrine tumors of the neovagina are discussed.